COMPARATIVE ANALYSIS OF TEACHER-CENTERED AND STUDENT-CENTERED APPROACHES IN ELEMENTARY SOCIAL STUDIES LEARNING - Wina Apriana; Trinda Farhan Satria; Rona Rossa (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
The shift in the 21st-century educational paradigm requires the implementation of student-centered learning to foster critical thinking, collaboration, and creativity among learners. This study aims to analyze the comparison between the implementation of Teacher-Centered Learning (TCL) and Student-Centered Learning (SCL) approaches in Social Studies learning at elementary schools. The research employed a descriptive qualitative approach combined with a survey method. The participants consisted of 30 elementary school Social Studies teachers in Padang City. Data were collected through interviews and documentation of students’ learning outcomes and analyzed using the Miles and Huberman interactive model, including data collection, data reduction, data display, and conclusion drawing. The findings revealed that the SCL approach, implemented through Problem-Based Learning, Discovery Learning, and Cooperative Learning models, provided more positive impacts than the TCL approach. SCL improved students’ cognitive achievement, encouraged active, collaborative, and confident attitudes, and enhanced psychomotor skills. In contrast, TCL tended to result in lower learning engagement, limited participation, and less optimal learning outcomes. These findings indicate that student-centered learning is more effective in supporting the achievement of Social Studies learning objectives in elementary schools. ABSTRAK Perubahan paradigma pendidikan abad ke-21 menuntut penerapan pembelajaran yang berpusat pada peserta didik guna mengembangkan kemampuan berpikir kritis, kolaboratif, dan kreatif. Penelitian ini bertujuan menganalisis perbandingan penerapan pendekatan Teacher-Centered Learning (TCL) dan Student-Centered Learning (SCL) dalam pembelajaran Ilmu Pengetahuan Sosial (IPS) di sekolah dasar. Penelitian menggunakan pendekatan kualitatif deskriptif yang dipadukan dengan metode survei. Subjek penelitian terdiri atas 30 guru IPS sekolah dasar di Kota Padang. Data dikumpulkan melalui wawancara dan dokumentasi hasil belajar peserta didik, kemudian dianalisis menggunakan teknik analisis data Miles dan Huberman yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pendekatan SCL yang diterapkan melalui model Problem Based Learning, Discovery Learning, dan Cooperative Learning memberikan dampak yang lebih positif dibandingkan TCL. Pendekatan SCL mampu meningkatkan hasil belajar kognitif, mendorong sikap aktif, kolaboratif, dan percaya diri, serta mengoptimalkan keterampilan psikomotor peserta didik. Sebaliknya, pendekatan TCL cenderung menghasilkan keterlibatan belajar yang lebih rendah, partisipasi yang terbatas, dan capaian belajar yang kurang optimal. Temuan ini menunjukkan bahwa penerapan pembelajaran yang berpusat pada peserta didik lebih efektif dalam mendukung pencapaian tujuan pembelajaran IPS di sekolah dasar.